New Life for Archaeological Collections - Ford, Ben M.; Allen, Rebecca, 1964- (Book collections on Project MUSE., 2019)
New Life for Archaeological Collections explores solutions to what archaeologists are calling the "curation crisis," that is, too much stuff with too little research, analysis, and public interpretation. This volume demonstrates how archaeologists are taking both large and small steps toward not only solving the dilemma of storage but recognizing the value of these collections through inventorying and cataloging, curation, rehousing, artifact conservation, volunteer and student efforts, and public exhibits. Essays in this volume highlight new questions and innovative uses for existing archaeological collections. Rebecca Allen and Ben Ford advance ways to make the evaluation and documentation of these collections more accessible to those inside and outside of the scholarly discipline of archaeology. Contributors to New Life for Archaeological Collections introduce readers to their research while opening new perspectives for scientists and students alike to explore the world of archaeology. These essays illuminate new connections between cultural studies and the general availability of archaeological research and information. Drawing from the experience of university professors, government agency professionals, and cultural resource managers, this volume represents a unique commentary on education, research, and the archaeological community.